„Muszę mieć maskę, wściekłą maskę”. Polemika z Marią Anną Potocką - Okołowicz, Stefan (WYDAWNICTWO NAUKOWE UNIWERSYTETU im. Adama Mickiewicza w Poznaniu, 2010)
Polemicising with Maria A. Potocka’s view, the author reflects on the problem of mask and facial expression in the life and work of S.I. Witkiewicz. They appear here as an expression of philosophy of man, a specific feature of the personality of the author of Szewcy [The Shoemakers] whose whole life, artistic and philosophical activity was marked by “facial expression”. The article also reminds the unusually important texts of Stefan Szuman, Witkacy’s friend, who points to the essence of Witkacy’s portraits. The last question discussed in this article is the problem of ascribing to Witkacy of the authorship of most of the photographs in which he is presented (since they are a documentation of his artistic creations) while actually the authors of these photographs are a dozen or so photographer friends of Witkacy.